More on Diamonds and De Beers - SKUBKO Yury Sergeevich (Ученые записки Института Африки Российской академии наук)
The author develops and supplements his previous analysis of a long period of Moscow’s confidential cooperation with South African diamond cartel De Beers, both forced and mutually beneficial, initially in the 1920s, then from late 1950s to early 1990s (Journal of the Institute for African Studies №3(40),2017). According to recently released documents such cooperation also continued between these two periods. It provided Soviet enterprises with imported industrial diamonds for precision instruments and augmented the country’s defense potential during the period of toughest Western Cold war sanctions in 1949–1953, before the discovery and extraction of rich deposits of Yakut diamonds. The article contains some interesting evidence of Russian diaspora involvement in South African industrial development. The author also calls for greater objectivity in historic analysis of the period of South African internal colonialism and anti-apartheid struggle.